Congenital paraesophageal hiatus hernia with gastric volvulus - Kshirsagar Ashok; Shinde S; Ahire M; Langade Y (Wolters Kluwer Medknow Publications, 2008)
Paraesophageal hiatus hernia is rarely seen in the neonatal period. An intrathoracic gastric volvulus complicating such a hernia is rarer. The upper gastrointestinal tract contrast study is diagnostic. Rapid diagnosis and treatment is essential. It avoids lethal complications as gastric dilatation, gangrene and perforation, which in turn may lead to cardiopulmonary arrest.